An Analysis of so-Called Export-Led Growth - Yang, Jie (International Monetary Fund, 2008)
The stylized fact that strong economic growth is usually accompanied with strong export growth leads many people to conclude that the export sector is the main driving force behind those episodes. The model in this paper, however, shows that the non-tradable sector may also generate high economic growth together with high export growth. Evidence shows that out of 71 ""so-called"" export-led growth episodes, only 37 of them are consistent with the ""exports driving growth"" hypothesis. Most of the remaining episodes (24 cases) experienced significant real exchange rate depreciation and are more likely to be characterized by ""growth driving exports